2021
DOI: 10.3390/healthcare9080967
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Training in Transgender Care on Healthcare Providers Competence and Confidence: A Cross-Sectional Survey

Abstract: All studies to date demonstrate a lack of access to care for transgender people. A few educational efforts in providing care to transgender people have been successful. However, one challenge in administering training is that there is almost no research on the need of healthcare providers (HCP) to acquire knowledge, as well as on the effect of training on their level of competence and confidence in working with transgender people. Results from an online survey of a convenience sample of HCP across four differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Results from an online survey among European healthcare professionals showed that only 52.7% reported some form of training on transgender health and that training led to increased confidence. 10 GPs had significantly lower confidence than nurses, psychosocial care providers, and other medical specialists. Ninety per cent of healthcare professionals believed that training would raise their competence, and this belief was significantly higher among professionals who had received some training.…”
Section: Getting Startedmentioning
confidence: 87%
See 2 more Smart Citations
“…Results from an online survey among European healthcare professionals showed that only 52.7% reported some form of training on transgender health and that training led to increased confidence. 10 GPs had significantly lower confidence than nurses, psychosocial care providers, and other medical specialists. Ninety per cent of healthcare professionals believed that training would raise their competence, and this belief was significantly higher among professionals who had received some training.…”
Section: Getting Startedmentioning
confidence: 87%
“…Ninety per cent of healthcare professionals believed that training would raise their competence, and this belief was significantly higher among professionals who had received some training. 10 …”
Section: Getting Startedmentioning
confidence: 99%
See 1 more Smart Citation
“…This culture needs to be built through the consistent, capillary, and specific education of HCP about LGBTQ+ lives, starting with the basic curricula. Without measures that specifically tackle the preparation of HCP on LGBTQ+ issues, healthcare systems are safe for some, and profoundly discriminatory for others [ 34 ]. Which leaves the principle of equal healthcare access to everyone failing to comply.…”
Section: Discussionmentioning
confidence: 99%
“…A transgender audiologist’s colleagues can be another significant source of prejudice and discrimination. Individual healthcare providers and healthcare systems that audiologists find themselves in are often sources of transphobia (Heng et al 2018), usually due to ignorance about transgender issues (Burgwal et al 2021; Korpaisarn & Safer 2018). Healthcare providers often do not use transgender people’s correct name and pronouns after being asked to, do not accept transgender people’s identity, and display a lack of professionalism when working with transgender people (Heng et al 2018).…”
Section: Transphobia In Colleaguesmentioning
confidence: 99%